Thoracic aortic computed tomography angiography in swine: establishment of a baseline for endovascular evaluation of the ascending aorta. (4th June 2020) - Tao, Li; Xianhao, Bao; Yuxi, Zhao; Ziwen, Li; Ziyi, Xu; Zhaoxiang, Zeng; Mingwei, Wu; Yiming, Li; Ding, Xu; Jiaxuan, Feng; Rui, Feng; Jian, Zhou; et al.
Abstract: OBJECTIVES: Our goal was to establish a baseline of computed tomography (CT) angiographic data for the porcine ascending thoracic aorta for endovascular evaluation of animal experiments and device development. METHODS: Thoracic aortic CT angiography was conducted on 49 pigs with an average body weight of 60–65 kg. The CT angiographic scans were done on an imaging reconstruction workstation to obtain the specific aortic geometric data, including the diameters of the planes, the heights among the planes and the clock positions of target arteries. RESULTS: Fourteen important planes were defined in the study for endograft customizing reference. The diameters of the planes were measured, and the heights among the planes were recorded. For endograft fenestrations, the right coronary artery ostium clock position was 100.11 ± 7.29°, and the brachiocephalic trunk ostium clock position was 74.72 ± 6.45°. The best projection angle of the tangent position of the left coronary artery was the right anterior oblique 17 ± 7° position. A pig with a rare congenital giant dilated aorta was found among the candidate experimental animals. CONCLUSIONS: For experimental porcine models, CT angiography has proved to be a suitable imaging technique. The established baseline angiography of the swine can provide reference values for future animal experiments and device development.